Antihyperlipidemic effect of selected pyrimidine derivatives mediated through multiple pathways. (2nd May 2021) - Irshad, Nadeem; Khan, Arif‐ullah; Shah, Fawad Ali; Nadeem, Humaira; Ashraf, Zaman; Tipu, Muhammad Khalid; Li, Shupeng
Abstract: Hyperlipidemia is worth‐mentioning risk factor in quickly expanding atherosclerosis, myocardial infarction, and stroke. This study attempted to determine effectiveness of selected pyrimidine derivatives: 5‐(3‐Hydroxybenzylidene)‐2, 4, 6( 1H, 3H, 5H )‐pyrimidinetrione (SR‐5), 5‐(4‐Hydroxybenzylidene)‐2, 4, 6( 1H, 3H, 5H )‐pyrimidinetrione (SR‐8), 5‐(3‐Chlorobenzylidene)‐2, 4, 6( 1H, 3H, 5H )‐pyrimidinetrione (SR‐9), and 5‐(4‐Chlorobenzylidene)‐2, 4, 6( 1H, 3H, 5H )‐pyrimidinetrione (SR‐10) against hyperlipidemia. In silico results revealed that SR‐5, SR‐8, SR‐9, and SR‐10 exhibited high affinity with 3‐hydroxy‐3‐methylglutaryl coenzyme A (HMGCoA) possessing binding energy values of −8.2, −8.4, −8.6, and −9.5 Kcal/mol, respectively, and moderate (<−8 Kcal/mol) against other selected targets. In vivo findings showed that test drugs (25 and 50 mg/Kg) significantly decreased HFD rat total cholesterol, triglycerides, low‐density lipoprotein, very‐low‐density lipoprotein, atherogenic index, coronary risk index, alkaline phosphatase, aspartate transaminase, alanine transaminase, and bilirubin and increased high‐density lipoprotein ( p < 0.05, p < 0.01, p < 0.001 vs HFD group). In animal liver tissues, SR‐5, SR‐8, SR‐9, and SR‐10 inhibited HMGCoA reductase enzyme, enhanced glutathione‐s‐transferase, reduced glutathione, catalase levels, improved cellular architecture in histopathological examination, and decreased expression of inflammatory markers: cyclo‐oxygenase 2, tumor necrosis factor alpha, phosphorylated c‐Jun N‐terminal kinase, and phosphorylated‐nuclear factor kappa B, evidenced in immunohistochemistry and enzyme‐linked immunosorbent assay molecular investigations. This study indicates that SR‐5, SR‐8, SR‐9, and SR‐10 exhibit antihyperlipidemic action, mediated possibly through HMGCoA inhibition, hepatoprotection, antioxidant, and anti‐inflammatory pathways.